Radio at war : a study of American radio propaganda and public opinion during World War II - Tan, Jovin Wen Lin (Nanyang Technological University, 2021)
Despite the great wealth of scholarly works on the relationship between wartime media and public opinion, as well as the medium's cultural importance since the 1920s, radio broadcasting continues to remain a much-neglected area of study in this field. Analysing domestic wartime radio programmes and national public opinion surveys, this paper thus aims to fill this gap in current literature by examining how American domestic propaganda during World War II reveal ideas surrounding influence, power and public opinion in times of war – more specifically, the role of media, particularly radio, in reflecting and swaying public attitudes towards government policies in the home front. Following America's experience in the Second World War, from the late 1930s to 40s, this paper primarily argues that the degree of effectiveness of US radio propaganda efforts in reaching the masses varied greatly and fluctuated constantly depending on a multitude of factors, including public and government attitudes and external circumstances, reaching its lowest point prior to America's formal entry into the war and its peak in the immediate months following the attack on Pearl Harbour.